Greenhouse Gas Emissions from Cities : Comparison of International Inventory Frameworks - Ibrahim, Nadine; Sugar, Lorraine; Hoornweg, Dan; Kennedy, Christopher (Taylor and Francis, 2013)
Credibly and consistently reporting greenhouse gas (GHG) emissions from cities and urban areas enables policy-makers and practitioners to contribute to addressing the challenge of climate change by meeting mitigation targets, and is critical to overall good municipal management. Good reporting allows for transparency, verification, and replication over time. This study provides an understanding of the GHG emissions inventory protocols and methodologies as they apply to cities. Though the inventories generally use common terminology, the differences in inventorying approaches are many, and the implications of the inventorying results at the city level are important to climate change policy and decision-makers. A compilation of GHG emissions inventory protocols is developed along with an analysis of their characteristics and inherent differences. Seven protocols are investigated: four are applied to Shanghai's community emissions; four to New York City's corporate emissions (i.e. those from municipal activities); and two to the reporting of Paris' emissions, including upstream components. The results show a significant degree of variability among the protocols.